Trends in Applied Intelligent Systems 23rd International Conference on Industrial Engineering and Other Applications of Applied Intelligent Systems, IEA/AIE 2010, Cordoba, Spain, June 1-4, 2010, Proceedings, Part III - Garca̕-Pedrajas, Nicols̀.; Herrera, Francisco.; Fyfe, Colin.; Bent̕ez, Jos ̌Manuel.; Ali, Moonis. (Lecture Notes in Computer Science, 2010)
The three volume set LNAI 6096, LNAI 6097, and LNAI 6098 constitutes the thoroughly refereed conference proceedings of the 23rd International Conference on Industrial Engineering and Other Applications of Applied Intelligend Systems, IEA/AIE 2010, held in Cordoba, Spain, in June 2010. The total of 119 papers selected for the proceedings were carefully reviewed and selected from 297 submissions.